2007
DOI: 10.1021/bi062217x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of cAMP-Dependent Protein Kinase Anchoring to the L-Type Calcium Channel Cav1.2 via A-Kinase Anchor Protein 150 in Neurons

Abstract: The cAMP-dependent protein kinase (PKA) regulates a wide array of cellular functions. In brain and heart PKA increases the activity of the L-type Ca2+ channel Cav1.2 in response to beta-adrenergic stimulation. Cav1.2 forms a complex with the beta2-adrenergic receptor, the trimeric GS protein, adenylyl cyclase, and PKA wherein highly localized signaling occurs [Davare, M. A., Avdonin, V., Hall, D. D., Peden, E. M., Burette, A., Weinberg, R. J., Horne, M. C., Hoshi, T., and Hell, J. W. (2001) Science 293, 98-101… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
159
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(168 citation statements)
references
References 84 publications
6
159
0
Order By: Relevance
“…Although we observed Yotiao, another abundant neuro- nal AKAP, in our lysates, we did not find that it co-immunoprecipitated with Ca V 1.2 channels, further verifying the specificity of this interaction. These results confirm the identification of AKAP15 in these co-immunoprecipitates as well as ␤ 2 ARs, MAP2B, and AKAP150 as reported previously (28,39). We have previously found that AKAP15 binds directly to cardiac Ca V 1.2 channels via the C-terminal LZ motif (24), so it is likely that the co-immunoprecipitation observed here reflects direct interaction between these two proteins.…”
Section: Resultssupporting
confidence: 92%
“…Although we observed Yotiao, another abundant neuro- nal AKAP, in our lysates, we did not find that it co-immunoprecipitated with Ca V 1.2 channels, further verifying the specificity of this interaction. These results confirm the identification of AKAP15 in these co-immunoprecipitates as well as ␤ 2 ARs, MAP2B, and AKAP150 as reported previously (28,39). We have previously found that AKAP15 binds directly to cardiac Ca V 1.2 channels via the C-terminal LZ motif (24), so it is likely that the co-immunoprecipitation observed here reflects direct interaction between these two proteins.…”
Section: Resultssupporting
confidence: 92%
“…AKAP150 KO and D36 mouse strains were generated as previously described (22,25,52). Briefly, the entire coding sequence of the AKAP150 (Akap5) gene (GenBank TM locus XM138063 position 2126 -2131) was replaced with a neomycin phosphotransferase cassette in AKAP150 KO mice by homologous recombination in embryonic stem cells in a 129S1/SvImJ background (Jackson Laboratories, Bar Harbor, ME).…”
Section: Methodsmentioning
confidence: 99%
“…We previously generated AKAP150 KO mice and mice that lack the PKA binding site at the C terminus of AKAP150 (D36 mice) (22,25,52). We showed earlier that PKA and its anchoring by AKAP150 plays an important role in LTP at an age of 2-3 weeks and again from 8 weeks on but not during 3-6 weeks (22).…”
mentioning
confidence: 99%
“…Previous studies showed that AKAP79/150 is abundant at the postsynaptic sites of glutamatergic synapses in which it facilitates PKA-dependent phosphorylation of AMPA and NMDA glutamate receptors, thereby contributing to synaptic plasticity (Colledge et al, 2000;Gomez et al, 2002;Lu et al, 2007). AKAP79/150 also associates with the L-type (Ca v 1.2) Ca 2ϩ channels (Gao et al, 1997;Hall et al, 2007), M-type (KCNQ2/3) K ϩ channels (Hoshi et al, 2003), ASIC1a and 2a channels (Chai et al, 2007), and ␤2-adrenergic receptor (Fraser et al, 2000).…”
Section: Trpv1 and Akap150 Are Coexpressed And Coimmunoprecipitate Inmentioning
confidence: 99%
“…We studied expression of four different AKAPs that have been shown to associate with other ion channels and receptors: AKAP15/18, AKAP150, AKAP250, and Yotiao (Wong and Scott, 2004). Immunoblots obtained from DRG and spinal cord lysates were compared with those obtained from brain, in which these AKAPs have been characterized previously (Tibbs et al, 1998;Westphal et al, 1999;Colledge et al, 2000;Piontek and Brandt, 2003;Hall et al, 2007;Lu et al, 2007).…”
Section: Trpv1 and Akap150 Are Coexpressed And Coimmunoprecipitate Inmentioning
confidence: 99%